Identification and Confirmation of Variables Influencing Manufacturer-Dealer Relationships for Steel and Allied Products - Dasari, Shailendra; Gunaseelan, Rupa; Suresh, Geetha (Indian Journal of Marketing, 2015)
Purpose: This study aimed to identify and confirm the variables influencing manufacturer-dealer relationships for steel and allied products. Approach and Methodology: The variables influencing manufacturer-dealer relationships were identified using exploratory factor analysis (EFA). Reliability and validity of the factors were established through confirmatory factor analysis using structural equation modeling. Findings: Eight factors accounting for 78% of the total variance were identified . Out of these, five are antecedents, one is a mediating variable, and the other two are outcome variables. Practical Relevance: Findings of this study would help manufacturers understand the variables that influence the channel relationships and research further into the dynamics of channel relationships for fine-tuning their strategies. Original Contribution: New constructs, that is, Supplier Critical Support and Supplier Versatility have been added to the existing body of literature, which in conjunction with the variables already identified and established by earlier scholars provide the framework for understanding the dynamics of channel relationships. A composite construct, that is, Relationship Strength was also conceptualized and operationalized. Research Type: Descriptive research conducted in a pre-determined geographical area.